Contribution of the Epstein-Barr virus to the oncogenesis of mature T-cell lymphoproliferative neoplasms - Barros, Mario Henrique M.; Alves, Paula Daniela S. (Frontiers in Oncology, 2023)
EBV is a lymphotropic virus, member of the Herpesviridae family that asymptomatically infects more than 90% of the human population, establishing a latent infection in memory B cells. EBV exhibits complex survival and persistence dynamics, replicating its genome through the proliferation of infected B cells or production of the lytic virions. Many studies have documented the infection of T/NK cells by EBV in healthy individuals during and after primary infection. This feature has been confirmed in humanized mouse models. Together these results have challenged the hypothesis that the infection of T/NK cells per se by EBV could be a triggering event for lymphomagenesis.Extranodal NK/T-cell lymphoma (ENKTCL) and Epstein-Barr virus (EBV)-positive nodal T-and NK-cell lymphoma (NKTCL) are two EBV-associated lymphomas of T/NK cells. These two lymphomas display different clinical, histological and molecular features. However, they share two intriguing characteristics: the association with EBV and a geographical prevalence in East Asia and